Mediasi Keputusan Pembelian pada Pengaruh Faktor Situasional dan Faktor Produk terhadap Kepuasan Konsumen Supermarket di Kota Kupang - Thom W. A. Isliko; Mintarti Rahayu (Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2012)
Mediating Purchasing decision at Influence Situasional Factor and Product Factor to Consumers satisfaction Supermarket in Kupang city. Purpose of research is to test factor influence consistency situasional and product factor to satisfaction of consumer through purchasing decision at supermarket in Kupang city. Research sample is consumer as decision taker, buyer and consumer shopping at supermarket Kupang city which amounts to 140. Sampling method applies technique Accidental Sampling. Descriptive analysis applies description score spread of research variable to. Analysis inferensial applies Confirmatory Factor Analysis (CFA) to test unidimensionality. Structural Equations Models (SEM). to test structure the relation and kontribution each variable as structure model former (Structural Models). Result of research of indication that factor situasional is meaning social environment, in perpective of former time and situation had influence to purchasing decision of consumer. Product factor meaning quality of product, fitur product and product mode has influence to consumer to do purchasing. Purchasing decision meaning preferensi purchasing, intention of purchasing, purchasing urgency and purchasing utility has influence to consumer satisfaction. Factor situasional and product factor has influence to consumer satisfaction through decision making Purchase. Testing consistency yielded by indication how well factor situasional and product factor can satisfy for going shopping/buying consumer at supermarket in Kupang city.Keywords: Situasional, Product, Purchasing Decision, Satisfaction of Consumer, Supermarket, Stuctural analysis model.